Positive electrode sheet and battery
Patent Information
- Application Number
- CN202311275832.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-09-28
AI Technical Summary
但是,使用大粒径的单晶镍锰酸锂材料将导致锂离子的扩散路径变长,界面扩散阻抗增大,在大倍率充放电时正极材料-电解液界面会产生较大的浓差极化,导致电池的循环性能变差
[0012](1)本发明提供的正极片,分区涂布多晶材料和单晶材料的设置,能够提高电池的循环性能。
Smart Images

Figure CN117199239B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically to a positive electrode and a battery. Background Technology
[0002] High-voltage spinel lithium nickel manganese oxide (LiNi) 0.5 Mn 1.5 O4 materials have a high voltage plateau (~4.7V vs. Li), a theoretical specific capacity of 146mAh / g, and an actual energy density of up to 600Wh / kg, thus showing good application prospects. However, lithium nickel manganese oxide has poor stability.
[0003] To improve the stability of lithium nickel manganese oxide (LiMO) materials, existing technologies have proposed using monocrystalline LiMO with a smaller specific surface area and a larger particle size. However, using large-particle-size monocrystalline LiMO materials will result in a longer lithium-ion diffusion path, increased interfacial diffusion resistance, and significant concentration polarization at the cathode material-electrolyte interface during high-rate charge and discharge, leading to poorer battery cycle performance.
[0004] Therefore, it is very meaningful to develop a positive electrode that can improve the cycle performance of batteries. Summary of the Invention
[0005] The purpose of this invention is to overcome the aforementioned problems in the prior art and provide a positive electrode sheet and a battery containing the positive electrode sheet. By employing a partitioned arrangement of different active material layers comprising monocrystalline spinel lithium nickel manganese oxide and polycrystalline spinel lithium nickel manganese oxide, the cycle performance of the battery is improved.
[0006] To achieve the above objectives, the first aspect of the present invention provides a positive electrode sheet, the positive electrode sheet comprising a positive current collector and a positive active material layer disposed on one or both surfaces of the positive current collector, wherein any one surface of the positive current collector comprises a first region and a second region, and the positive active material layer comprises a first active material layer and a second active material layer, wherein the first active material layer is disposed in the first region and the second active material layer is disposed in the second region;
[0007] Wherein, the first active material layer includes a first spinel lithium nickel manganese oxide, and the second active material layer includes a second spinel lithium nickel manganese oxide;
[0008] The first spinel lithium nickel manganese oxide includes monocrystalline spinel lithium nickel manganese oxide, and the second spinel lithium nickel manganese oxide includes polycrystalline spinel lithium nickel manganese oxide.
[0009] In some embodiments, a tab is provided on the side of the second active material layer away from the first active material layer.
[0010] A second aspect of the present invention provides a battery comprising the positive electrode sheet described in the first aspect of the present invention.
[0011] The present invention, by adopting the above technical solution, has the following beneficial effects:
[0012] (1) The positive electrode provided by the present invention, with the setting of partitioned coating of polycrystalline material and single crystal material, can improve the cycle performance of the battery.
[0013] (2) Furthermore, the positive electrode provided by the present invention is coated with polycrystalline material near the tab and with single crystal material away from the tab, which can reduce electrochemical polarization and concentration polarization, reduce polarization internal resistance, thereby reducing the DC internal resistance DCR and Mn dissolution phenomenon of the battery.
[0014] (3) Furthermore, the positive electrode provided by the present invention, by doping different elements in single-crystal lithium nickel manganese oxide and polycrystalline lithium nickel manganese oxide, can further reduce the polarization internal resistance of the positive electrode during the charging and discharging process, reduce the DCR growth during the cycle process, and reduce the Mn dissolution phenomenon.
[0015] (4) The battery provided by the present invention has a lower DC internal resistance (DCR), better cycle performance and higher electrochemical stability.
[0016] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values close to those ranges or values. For numerical ranges, endpoint values of various ranges, endpoint values of various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In this document, unless otherwise specified, data ranges include endpoints. Attached Figure Description
[0017] Figure 1 The figure shown is a planar schematic diagram of the die-cut positive electrode sheet along its length in an example.
[0018] Reference numerals: 1-First active material layer; 2-Second active material layer; 3-Taper. Detailed Implementation
[0019] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0020] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.
[0021] A first aspect of the present invention provides a positive electrode sheet, the positive electrode sheet comprising a positive current collector and a positive active material layer disposed on one or both surfaces of the positive current collector; any one surface of the positive current collector comprises a first region and a second region, the positive active material layer comprises a first active material layer and a second active material layer, the first active material layer being disposed in the first region and the second active material layer being disposed in the second region; wherein the first active material layer comprises a first spinel lithium nickel manganese oxide, and the second active material layer comprises a second spinel lithium nickel manganese oxide; the first spinel lithium nickel manganese oxide comprises monocrystalline spinel lithium nickel manganese oxide, and the second spinel lithium nickel manganese oxide comprises polycrystalline spinel lithium nickel manganese oxide.
[0022] It should be noted that the first active material layer includes, in addition to the first spinel lithium nickel manganese oxide, components such as the first conductive agent and the first binder; the second active material layer includes, in addition to the second spinel lithium nickel manganese oxide, components such as the second conductive agent and the second binder. The specific types of the first conductive agent, the second conductive agent, the first binder and the second binder are not limited, and conductive agents and binders used in the art can be selected according to actual needs.
[0023] In this invention, "single-crystal spinel lithium nickel manganese oxide" refers to each active material single-crystal spinel lithium nickel manganese oxide particle being a primary crystal with a relatively large particle size; "polycrystalline spinel lithium nickel manganese oxide" refers to each active material polycrystalline spinel lithium nickel manganese oxide particle being an agglomeration of multiple primary crystal particles with a smaller particle size. The single-crystal and polycrystalline states can be verified by particle size characterization through electrode SEM testing.
[0024] The inventors of this invention discovered that when the positive electrode active material layer contains only single-crystal spinel lithium nickel manganese oxide (single-crystal active material), the Dv50 of the single-crystal active material is generally smaller than that of the polycrystalline active material, while its specific surface area is larger, its electrode compaction density is higher, and it can withstand greater lattice stress. However, its lithium insertion / extraction speed is slower and its path is longer than that of the polycrystalline material, making it more prone to polarization during charge and discharge, resulting in a faster increase in DCR. Conversely, when the positive electrode active material layer contains only spinel lithium nickel manganese oxide (polycrystalline active material), the Dv50 of the polycrystalline active material is generally larger than that of the single-crystal active material, while its specific surface area is smaller, its electrode compaction density is lower, its contact area with the electrolyte is smaller, and its lithium ion insertion / extraction path is shorter (because it is composed of many small-diameter primary particles aggregated together). However, the structural stability of small particles is not as strong as that of large single crystals, making them more susceptible to Mn dissolution during cycling due to structural decay, thus deteriorating battery performance.
[0025] Furthermore, based on the above-mentioned problems, the inventors of this invention proposed dividing the positive electrode current collector into a first region and a second region, coating the first region with an active material layer containing monocrystalline spinel lithium nickel manganese oxide, and coating the second region with an active material layer containing polycrystalline spinel lithium nickel manganese oxide. This partitioned coating of polycrystalline and monocrystalline materials can reduce the electrochemical polarization and concentration polarization generated at the positive electrode material-electrolyte interface to a certain extent, thereby improving the cycle performance of the battery.
[0026] To further improve the effect, one or more of the technical features can be further optimized.
[0027] In some embodiments, a tab is provided on the side of the second active material layer away from the first active material layer. That is, the second active material layer is disposed on the side closer to the tab, and the first active material layer is disposed on the side away from the tab. Figure 1 As shown, a first active material layer 1 and a second active material layer 2 are disposed on the positive electrode sheet, and a tab 3 is disposed on the side of the second active material layer 2 away from the first active material layer 1.
[0028] The inventors of this invention discovered that when the crystal grain size of the positive electrode active material is large, the low migration rate of lithium ions leads to an electrochemical reaction rate lower than the electron transport rate, resulting in significant electrochemical polarization. Therefore, this invention coats a second active material layer near the tab in the positive electrode sheet. This second layer contains polycrystalline spinel lithium nickel manganese oxide with a short lithium ion diffusion path, allowing for rapid lithium ion insertion / extraction and extraction. This reduces electrochemical polarization and concentration polarization to some extent, lowering polarization resistance and thus reducing DC resistance (DCR). A first active material layer, containing large-particle-size single-crystal spinel lithium nickel manganese oxide, is coated away from the tab to reduce Mn dissolution.
[0029] Furthermore, the inventors of this invention discovered that while coating polycrystalline spinel lithium nickel manganese oxide near the tab can have the aforementioned advantages, coating the entire positive electrode with polycrystalline spinel lithium nickel manganese oxide can lead to excessively high Mn dissolution rates, degrading battery performance, and Mn deposition on the negative electrode, affecting battery capacity retention and causing short circuits. Therefore, the inventors further discovered that, in addition to coating polycrystalline spinel lithium nickel manganese oxide near the tab, coating single-crystal spinel lithium nickel manganese oxide further away from the tab, and adjusting the ratio of the coating lengths of polycrystalline and single-crystal spinel lithium nickel manganese oxide, can reduce Mn dissolution during charging and discharging, lower the battery's DCR, and improve the electrochemical stability during battery cycling.
[0030] In some embodiments, the length of the first region is d1, the length of the second region is d2, and the relationship between d1 and d2 satisfies: 0.5≤d1 / d2≤15.
[0031] It should be noted that when the positive electrode is rectangular, the widths of the first and second regions are independently the same as the width of the positive electrode. The lengths of the first and second regions are independently the horizontal distances along the length of the positive electrode. When the positive electrode is square, the width or length of the first and second regions are independently the same as the width or length of the positive electrode.
[0032] In some embodiments, the tab arrangement is similar to that in a stacked battery. A stacked battery generally consists mainly of stacked positive electrode plates, negative electrode plates, and separators, with the separators spaced between each positive and negative electrode plate. Positive and negative electrode plates are welded or riveted to the tab welding positions on each positive and negative electrode plate, and then the positive electrode plates on each positive electrode plate are connected together, and the negative electrode plates on each negative electrode plate are connected together.
[0033] In some embodiments, the ratio of d1 / d2 can be 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15.
[0034] By controlling the d1 / d2 ratio within the aforementioned range and further optimizing it, we can avoid situations where an excessively large d1 / d2 ratio results in insufficient coating of polycrystalline spinel nickel-manganese lithium oxide, leading to an insignificant improvement in the lithium-ion insertion / extraction rate near the tab of the positive electrode and poor reduction in polarization resistance. Conversely, we can avoid an excessively small d1 / d2 ratio, which would result in excessive coating of polycrystalline spinel nickel-manganese lithium oxide on the positive electrode, leading to an excessively high Mn dissolution rate and affecting the battery capacity retention rate.
[0035] In some embodiments, the relationship between d1 and d2 satisfies: 3≤d1 / d2≤7, preferably 4≤d1 / d2≤6. In the positive electrode active material, single-crystal spinel lithium nickel manganese oxide is predominant, with polycrystalline spinel lithium nickel manganese oxide near the tab as a secondary component. This avoids excessive polarization due to the high current density at the tab, thus preventing excessively rapid DCR growth. Simultaneously, single-crystal materials exhibit stronger stability and less Mn dissolution compared to pure polycrystalline spinel lithium nickel manganese oxide or materials dominated by polycrystalline spinel lithium nickel manganese oxide.
[0036] Spinel lithium nickel manganese oxide has a high voltage plateau, high theoretical specific capacity and high actual energy density, making it very suitable for use in this invention.
[0037] In some embodiments, the chemical formula of the spinel lithium nickel manganese oxide is Li a Ni x Mn y M zO4, where M is any one or more combinations of doping elements selected from Al, Mg, Ti, Zr, Na, Fe, Y, W, Sr, P, F, Nb, Ta, Mo, and V; 0.45≤x≤0.50, 1.45≤y≤1.50, 0≤z≤0.01, and 0.9≤a≤1.1. Doping with metal elements can improve the stability of spinel lithium nickel manganese oxide, reduce side reactions between spinel lithium nickel manganese oxide and the electrolyte, suppress Mn dissolution, and improve cycle stability.
[0038] In some embodiments, the doping element in the single-crystal lithium nickel manganese oxide includes any one or a combination of two of Nb and P. Nb doping makes the edges of the single-crystal particles smoother, reducing the interfacial impedance for lithium-ion insertion / extraction at the edges, thereby reducing the polarization resistance during charging and discharging and decreasing DCR growth during cycling. High-valence P doping increases the conductivity of large-particle-size single-crystal materials, thereby reducing ohmic resistance and achieving the goal of reducing DCR growth.
[0039] In some embodiments, the doping elements in the polycrystalline lithium nickel manganese oxide include any one or more combinations of Al, Zr, and Ti. Al, Zr, and Ti elements can all enhance crystal structure stability and improve Mn dissolution during long-term cycling.
[0040] In some embodiments, the Dv50 of the single-crystal spinel lithium nickel manganese oxide is 2μm to 10μm, preferably 3μm to 8μm. Limiting the Dv50 of the single-crystal spinel lithium nickel manganese oxide to the above range can avoid the problem that an excessively large Dv50 of the single crystal will lead to excessive DCR growth and a drop in cycling performance; it can also avoid the problem that an excessively small Dv50 of the single crystal will lead to excessive specific surface area, excessive Mn dissolution, and low capacity retention.
[0041] In some embodiments, the Dv50 of the polycrystalline spinel lithium nickel manganese oxide is 5 μm to 20 μm, preferably 6 μm to 15 μm. Keeping the Dv50 of the polycrystalline spinel lithium nickel manganese oxide within the above range avoids an excessively large Dv50, which would lead to a decrease in compaction density and be detrimental to improving battery energy density; it also avoids an excessively small Dv50, which would result in an excessively large specific surface area, leading to greater Mn dissolution and a greater DCR increase for the same particle size.
[0042] Furthermore, when the Dv50 of both monocrystalline and polycrystalline spinel lithium nickel manganese oxide is controlled within the above-mentioned and preferred ranges, the overall diffusion of lithium ions in monocrystalline and polycrystalline spinel lithium nickel manganese oxide can be further improved, the DCR growth can be reduced, the Mn dissolution can be reduced, and the battery energy density and capacity retention can be improved.
[0043] In some embodiments, the Dv50 of monocrystalline spinel lithium nickel manganese oxide is less than that of polycrystalline spinel lithium nickel manganese oxide, which is beneficial for increasing lithium-ion diffusion, improving battery capacity retention, and reducing battery DCR.
[0044] Furthermore, the synergistic effect of the Dv50 of monocrystalline and polycrystalline spinel lithium nickel manganese oxide with the coating length ratio of the aforementioned monocrystalline and polycrystalline spinel lithium nickel manganese oxide can further reduce Mn dissolution and lower the DCR of the battery, thereby further improving the electrochemical stability of the battery during cycling.
[0045] In some embodiments, the polycrystalline spinel lithium nickel manganese oxide comprises n primary particles, where n is 10 to 500, and the Dv50 of the primary particles is 0.5 μm to 2 μm, preferably 0.8 μm to 1.5 μm.
[0046] In polycrystalline spinel nickel-manganese lithium oxide with the same Dv50, controlling the Dv50 of the primary particles within the aforementioned range can prevent excessive Mn dissolution due to an excessively small Dv50, and also prevent a reduced compaction density due to an excessively large Dv50, which is detrimental to energy density improvement, as well as excessive polarization during charge and discharge. A Dv50 within the aforementioned range can reduce the specific surface area, thereby reducing Mn dissolution and further reducing the battery's DCR, thus improving the cycle performance of the cathode.
[0047] In some embodiments, the thickness of the first active material layer is 100 μm to 200 μm.
[0048] In some embodiments, the thickness of the second active material layer is 100 μm to 200 μm.
[0049] The thickness of the first active material layer is the same as that of the second active material layer, which can avoid the deterioration of electrochemical performance caused by unevenness of the electrode surface due to different thicknesses.
[0050] In some embodiments, the content of the single-crystal spinel lithium nickel manganese oxide is 90wt%-99wt%, preferably 94wt%-96wt%, based on the total weight of the first active material layer.
[0051] In some embodiments, the content of the polycrystalline spinel lithium nickel manganese oxide is 90wt%-99wt%, preferably 94wt%-96wt%, based on the total weight of the second active material layer.
[0052] When the content of monocrystalline spinel lithium nickel manganese oxide in the first active material layer is controlled within the above range, and the content of polycrystalline spinel lithium nickel manganese oxide in the second active material layer is controlled within the above range, it can be ensured that the first active material layer and the second active material layer contain sufficient amounts of monocrystalline spinel lithium nickel manganese oxide and polycrystalline spinel lithium nickel manganese oxide, respectively, thereby further increasing the capacity of the positive electrode sheet per unit area, and thus increasing the energy density of the battery containing the electrode sheet.
[0053] The present invention also provides a method for preparing the positive electrode sheet, comprising the following steps:
[0054] (1) Weigh a certain amount of single crystal spinel lithium nickel manganese oxide, mix it with the first conductive agent and the first binder in a certain proportion, and dissolve it with the first organic solvent to obtain the first positive electrode slurry.
[0055] A certain amount of polycrystalline spinel lithium nickel manganese oxide is weighed out, mixed with a second conductive agent and a second binder in a certain proportion, and dissolved in a second organic solvent to obtain a second positive electrode slurry.
[0056] (2) The first positive electrode slurry obtained in step (1) is coated on one or both sides of the positive electrode current collector, with a coating length of d1; the second positive electrode slurry obtained in step (1) is coated on one or both sides of the positive electrode current collector, connected to the position where the first positive electrode slurry is coated, with a coating length of d2. The relationship between d1 and d2 satisfies: 0.5≤d1 / d2≤15.
[0057] (3) The positive electrode is obtained by drying, rolling and slitting the electrode after coating with slurry.
[0058] Furthermore, the method for preparing the positive electrode sheet according to the present invention can be flexibly adjusted according to the process. For example, the coating length of different slurries is not limited during coating, and the ratio of d1 to d2 can be satisfied during slitting.
[0059] In some embodiments, the positive current collector is a material that is conductive and will not cause adverse chemical changes in the secondary battery, including but not limited to aluminum, aluminum alloys, nickel, nickel alloys, titanium, and titanium alloys.
[0060] In some embodiments, the first conductive agent and the second conductive agent are independently selected from at least one of conductive carbon black (SP), acetylene black, Ketjen black, graphene, conductive carbon fiber, 350G, carbon nanotubes (CNTs), metal powder, and carbon fiber. Preferably, the first conductive agent and the second conductive agent are the same.
[0061] In some embodiments, the first adhesive and the second adhesive are independently selected from at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber (SBR), polytetrafluoroethylene, and polyethylene oxide. Preferably, the first adhesive and the second adhesive are the same.
[0062] In some embodiments, the first organic solvent and the second organic solvent are independently selected from at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N-ethylpyrrolidone (NEP), and dimethylacetamide (DMAC), acetone, methanol, ethanol, and diethyl ether. Preferably, the first organic solvent and the second organic solvent are the same.
[0063] A second aspect of the present invention provides a battery comprising the positive electrode sheet described in the first aspect of the present invention.
[0064] The battery of the present invention, due to the inclusion of the above-mentioned positive electrode, has a lower DC internal resistance (DCR), better cycle performance, and higher electrochemical stability.
[0065] In some embodiments, the battery is a lithium-ion battery.
[0066] In some embodiments, the battery is a stacked lithium-ion battery, i.e., a stacked battery. Stacked batteries have higher space utilization of the cell, which is beneficial for improving energy density; the reaction rate is consistent across all parts of the stacked structure, reducing internal polarization caused by partitioned coating; the stacked structure with multiple electrodes in parallel helps reduce internal resistance and has better rate performance, which is very compatible with the material characteristics of spinel nickel manganese oxide. Spinel nickel manganese oxide exhibits rapid DCR growth during cycling, especially at high temperatures; furthermore, spinel nickel manganese oxide has good charge-discharge performance, and the stacked structure helps to fully utilize its performance advantages.
[0067] In some embodiments, the battery further includes a negative electrode. After 300 cycles, the Mn content in the negative electrode is 10–10000 ppm, preferably 10–500 ppm, and more preferably 10–300 ppm. Controlling the manganese content in the negative electrode within the above range can effectively reduce Mn leaching from the positive electrode, reduce Mn deposition on the negative electrode, improve battery capacity retention, reduce battery short-circuit problems, and improve battery cycle performance and safety.
[0068] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a layer of negative electrode active material coated on one or both surfaces of the negative electrode current collector.
[0069] For example, the negative electrode current collector is a material that is conductive and will not cause adverse chemical changes in the secondary battery, and may be selected from copper, stainless steel, aluminum, nickel, titanium, carbon cloth or a composite of said materials.
[0070] The negative electrode active material layer comprises a negative electrode active material, a conductive agent, and a binder. The negative electrode active material is selected from artificial graphite, natural graphite, soft carbon, hard carbon, or materials containing 1-20 wt% SiO₂.x at least one of C or Si / C graphite composite materials, wherein 0<x<2. Preference is given to artificial graphite and / or natural graphite.
[0071] In some embodiments, the battery further comprises an electrolyte, and the electrolyte comprises an electrolyte salt, an organic solvent, and optionally an additive.
[0072] In some embodiments, the electrolyte salt may be selected from one or a combination of several of LiPF₆ (lithium hexafluorophosphate), LiBF₄ (lithium tetrafluoroborate), LiClO₄ (lithium perchlorate), LiAsF₆ (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluoro(oxalato)borate), LiBOB (lithium bis(oxalato)borate), LiPO₂F₂ (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalato)phosphate) and LiTFOP (lithium tetrafluoro(oxalato)phosphate).
[0073] In some embodiments, the organic solvent may be selected from one or a combination of several of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0074] In some embodiments, the electrolyte may further optionally include an additive. For example, the additive may include a negative electrode film-forming additive (such as fluoropropylene carbonate, 1,3-propane sultone, 1,3-propene sultone, vinyl sulfate, etc.), may also include a positive electrode film-forming additive (such as tris(2,2,2-trifluoroethyl) phosphite (TFEP), trimethyl phosphite (TMP), tris(pentafluorophenyl)phosphine (TPFPP), etc.), and may further include an additive capable of improving certain performances of the battery, such as an additive for improving the overcharge performance of the battery (such as xylene, phenylcyclohexane, etc.), an additive for improving high-voltage stability (such as fluoroethylene carbonate), and the like.
[0075] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0076] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0077] The present invention will now be described in detail with reference to specific embodiments, which are intended to understand rather than limit the invention.
[0078] The lithium-ion batteries in the following examples and comparative examples were all prepared according to the following method, the only difference being the positive electrode sheet. The specific differences between the positive electrode plates are shown in Table 1. .
[0079] 1. Preparation of positive electrode sheet
[0080] (1) Weigh appropriate amounts of monocrystalline lithium nickel manganese oxide and polycrystalline lithium nickel manganese oxide (molecular formulas shown in Table 1), and dissolve them in NMP solvent according to a mass ratio of spinel lithium nickel manganese oxide: carbon black: PVDF of 95:2.5:2.5 to obtain monocrystalline slurry and polycrystalline slurry, respectively. The solid content of the monocrystalline slurry is 65-68%; the solid content of the polycrystalline slurry is 68-70%; and the viscosity of both is 3000-8000 mPa·s.
[0081] (2) The monocrystalline paste and polycrystalline paste are coated on both sides of the positive current collector aluminum foil, respectively. The coating length of the monocrystalline paste is d1 and the coating length of the polycrystalline paste is d2. The positive electrode sheet is dried, rolled and die-cut to obtain the corresponding positive electrode sheet.
[0082] To ensure the test data is comparable, the positive electrode size is kept consistent in all embodiments and comparative examples, with the coating length (d1+d2) of the fixed positive electrode being 6 cm.
[0083] 2. Preparation of negative electrode sheet
[0084] A slurry is prepared by wet process using artificial graphite anode material (96% by weight), conductive carbon black (SP) conductive agent (1.5% by weight), sodium carboxymethyl cellulose (CMC) binder (0.7% by weight), and styrene-butadiene rubber (SBR) binder (1.8% by weight). The slurry is coated on the surface of copper foil for the anode current collector, and then dried (temperature: 85℃, time: 5h), rolled and die-cut to obtain the anode sheet.
[0085] 3. Preparation of the diaphragm
[0086] A 2μm thick titanium oxide layer is coated on one side of a 5μm thick polyethylene diaphragm, and a 1μm thick polyvinylidene fluoride-hexafluoropropylene copolymer composite layer is coated on both sides.
[0087] 4. Stack the above positive electrode, negative electrode, and separator into a certain number of layers to obtain a stacked battery, wherein the separator is located between the positive and negative electrodes; then place the obtained stacked core into an aluminum-plastic film, inject electrolyte (containing 1M lithium hexafluorophosphate, the solvent being a mixed solvent of ethylene carbonate / dimethyl carbonate / 1,2-propylene glycol carbonate in a 1:1:1 (volume ratio) mixture), vacuum seal, age, form (charged to 4.5V at 0.2C), re-seal, capacity sorting and other processes to obtain the corresponding soft-pack stacked lithium-ion battery.
[0088] Table 1
[0089]
[0090]
[0091]
[0092] Note: " / " indicates that the material was not added.
[0093] In Example 1, the ratio of d1 / d2 was mainly changed; in Example 2, different elements were doped into the single crystal and polycrystalline materials; in Example 3, the single crystal Dv50 was mainly changed; in Example 4, the polycrystalline Dv50 was mainly changed; in Example 5, the particle size of the primary particles in the polycrystalline material was mainly changed; in Example 6, the number of primary particles in the polycrystalline material was mainly changed; and in Examples 7 and 8, the particle sizes of both the single crystal and polycrystalline materials were changed simultaneously.
[0094] The relevant performance tests of the positive electrode and battery in the above embodiments and comparative examples are described below:
[0095] (1) Cyclic test: At an ambient temperature of 25℃, the battery cell was subjected to 1C / 1C charge and discharge test within a voltage range of 3.45-4.9V. The charging process was 1C charging to the upper limit voltage and then constant voltage charging to 0.05C. There was a 30min interval between each charge and discharge. The test results are recorded in Table 2.
[0096] (2) DCR test: After the battery has completed 300 cycles of testing, it is charged and discharged at 0.1C / 0.1C for 1 week, then charged to 50% SOC, and then discharged at 3C for 10 seconds on the charging and discharging equipment to obtain the corresponding DCR value. The test results are recorded in Table 2.
[0097] (3) Mn content test: The fully discharged battery was disassembled to obtain the negative electrode sheet. The negative electrode sheet was cut into pieces and dissolved with dilute hydrochloric acid. Then, the foil and filtrate were separated by ultrasonic water bath heating treatment. The filtrate was diluted to a 50mL volumetric flask and the Mn content was tested by ICP. The test results are recorded in Table 2.
[0098] Table 2
[0099]
[0100] As can be seen from the data in Table 2, coating polycrystalline spinel lithium nickel manganese oxide near the tab and coating monocrystalline spinel lithium nickel manganese oxide away from the tab, with the d1 / d2 ratio within a suitable range, can reduce Mn dissolution, lower DCR, and improve capacity retention.
[0101] The results from Example 1 show that a high d1 / d2 ratio results in less polycrystalline spinel lithium nickel manganese oxide material being coated, leading to a less significant increase in the lithium-ion insertion / extraction rate near the tab of the positive electrode and a poor effect on reducing polarization resistance. A low d1 / d2 ratio results in excessive coating of polycrystalline spinel lithium nickel manganese oxide material on the positive electrode, leading to an excessively high dissolution rate of transition Mn elements and affecting the battery capacity retention rate.
[0102] The results from Example 2 show that doping single-crystal spinel lithium nickel manganese oxide with Nb and P elements, and polycrystalline spinel lithium nickel manganese oxide with Al, Zr, and Ti elements, can reduce the polarization resistance of the positive electrode during charging and discharging, reduce the DCR growth during cycling, and improve the Mn dissolution phenomenon during long cycling.
[0103] The results of Examples 3 and 4 show that when the Dv50 of monocrystalline spinel lithium nickel manganese oxide and polycrystalline spinel lithium nickel manganese oxide are within the protection scope of this invention, they are beneficial to reduce Mn dissolution, lower DCR, and improve capacity retention.
[0104] The results from Examples 5 and 6 show that when the particle size and number of primary polycrystalline particles are within the scope of protection of this invention, it is beneficial to reduce Mn leaching, lower DCR, and improve capacity retention.
[0105] The results of Examples 7 and 8 show that when the Dv50 of both monocrystalline spinel lithium nickel manganese oxide and polycrystalline spinel lithium nickel manganese oxide is too large and exceeds the protection scope of this invention, it will lead to excessive DCR growth. When the Dv50 of both monocrystalline spinel lithium nickel manganese oxide and polycrystalline spinel lithium nickel manganese oxide is too small and exceeds the protection scope of this invention, it will lead to excessive Mn dissolution.
[0106] The results of Comparative Examples 1 and 2 show that coating monocrystalline spinel lithium nickel manganese oxide alone will cause excessive DCR growth; coating polycrystalline spinel lithium nickel manganese oxide alone will cause excessive Mn dissolution, and the dissolution of Mn will destroy the crystal structure of the polycrystalline cathode material, which will also lead to DCR growth.
[0107] Finally, it is particularly noted that all the technical features of this invention have a synergistic effect. To further improve battery performance, it is recommended that all technical features be adopted during battery production to achieve a comprehensive improvement in battery performance.
[0108] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element. Furthermore, it should be noted that the scope of the methods and apparatuses in the embodiments of this application is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. Additionally, features described with reference to certain examples may be combined in other examples.
[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A positive electrode plate, characterized in that, The positive electrode sheet includes a positive current collector and a positive active material layer disposed on one or both surfaces of the positive current collector; any one surface of the positive current collector includes a first region and a second region, and the positive active material layer includes a first active material layer and a second active material layer, wherein the first active material layer is disposed in the first region and the second active material layer is disposed in the second region; Wherein, the first active material layer includes a first spinel lithium nickel manganese oxide, and the second active material layer includes a second spinel lithium nickel manganese oxide; The first spinel lithium nickel manganese oxide includes monocrystalline spinel lithium nickel manganese oxide, and the second spinel lithium nickel manganese oxide includes polycrystalline spinel lithium nickel manganese oxide.
2. The positive electrode sheet according to claim 1, characterized in that, A tab is provided on the side of the second active material layer away from the first active material layer.
3. The positive electrode sheet according to claim 1, characterized in that, The length of the first region is d1, and the length of the second region is d2. The relationship between d1 and d2 is: 0.5≤d1 / d2≤15.
4. The positive electrode sheet according to claim 3, characterized in that, The relationship between d1 and d2 satisfies: 3≤d1 / d2≤7.
5. The positive electrode sheet according to claim 3, characterized in that, The relationship between d1 and d2 satisfies: 4≤d1 / d2≤6.
6. The positive electrode sheet according to claim 1, characterized in that, The chemical formula of the spinel lithium nickel manganese oxide is Li a Ni x Mn y M z O4, where M is any one or more combinations of doping elements Al, Mg, Ti, Zr, Na, Fe, Y, W, Sr, P, F, Nb, Ta, Mo, and V; 0.45≤x≤0.50, 1.45≤y≤1.50, 0≤z≤0.01, and 0.9≤a≤1.
1.
7. The positive electrode sheet according to claim 6, characterized in that, The doping elements in the single-crystal spinel lithium nickel manganese oxide include any one or a combination of two of Nb and P. And / or, the doping elements in the polycrystalline spinel lithium nickel manganese oxide include any one or more combinations of Al, Zr, and Ti.
8. The positive electrode sheet according to any one of claims 1-7, characterized in that, The Dv50 of the single-crystal spinel lithium nickel manganese oxide is 2 μm to 10 μm; And / or, the Dv50 of the polycrystalline spinel lithium nickel manganese oxide is 5 μm to 20 μm.
9. The positive electrode sheet according to any one of claims 1-7, characterized in that, The Dv50 of the single-crystal spinel lithium nickel manganese oxide is 3 μm to 8 μm; And / or, the Dv50 of the polycrystalline spinel lithium nickel manganese oxide is 6 μm to 15 μm.
10. The positive electrode sheet according to any one of claims 1-7, characterized in that, The Dv50 of the single-crystal spinel lithium nickel manganese oxide is less than that of the polycrystalline spinel lithium nickel manganese oxide.
11. The positive electrode sheet according to any one of claims 1-7, characterized in that, The polycrystalline spinel lithium nickel manganese oxide comprises n primary particles, where n ranges from 10 to 500.
12. The positive electrode sheet according to claim 11, characterized in that, The Dv50 of the primary particles is 0.5μm~2μm.
13. The positive electrode sheet according to claim 1, characterized in that, Based on the total weight of the first active material layer, the content of the single-crystal spinel lithium nickel manganese oxide is 90wt%-99wt%; And / or, based on the total weight of the second active material layer, the content of the polycrystalline spinel lithium nickel manganese oxide is 90wt%-99wt%.
14. A battery, characterized in that, Includes the positive electrode sheet as described in any one of claims 1-13.
15. The battery according to claim 14, characterized in that, The battery also includes a negative electrode, and after 300 cycles, the content of Mn in the negative electrode is 10~10000ppm.
16. The battery according to claim 15, characterized in that, After the battery has undergone 300 cycles, the Mn content in the negative electrode is 10~500ppm.
17. The battery according to claim 15, characterized in that, After the battery has undergone 300 cycles, the Mn content in the negative electrode is 10~300ppm.
18. The battery according to any one of claims 14-17, characterized in that, The battery includes stacked cells.
Citation Information
Patent Citations
Secondary battery and electronic device
CN116581284A
Positive electrode active material and preparation method and application thereof
CN116802843A